l need to understand how to figure this problem out

## -2(r+6)=r-18

Tutors, please sign in to answer this question.

# 1 Answer

First, I would distribute the -2 to get -2r - 12 = r - 18.

Then get all the terms with variables to the same side by adding 2r to both sides.

-2r - 12 + 2r = r - 18 + 2r

This simplifies to -12 = 3r - 18.

Now add 18 to both sides to get all the constant terms on the same side.

-12 + 18 = 3r - 18 + 18

This simplifies to 6 = 3r.

To finish solving for r, divide both sides by 3.

6/3 = 3r/3.

This simplifies to 2 = r.